A Clinician's Primer for Idiographic Research: Considerations and Recommendations. Issue 5 (September 2019) - Piccirillo, Marilyn L.; Beck, Emorie D.; Rodebaugh, Thomas L.
Abstract: Theorists and clinicians have long noted the need for idiographic (i.e., individual-level) designs within clinical psychology. Results from idiographic work may provide a possible resolution of the therapist's dilemma— the problem of treating an individual using information gathered via group-level research. Due to advances in data collection and time series methodology, there has been increasing interest in using idiographic designs to answer clinical questions. Although time series methods have been well-studied outside the field of clinical psychology, there is limited direction on how clinicians can use such models to inform their clinical practice. In this primer, we collate decades of published and word-of-mouth information on idiographic designs, measurement, and modeling. We aim to provide an initial guide on the theoretical and practical considerations that we urge interested clinicians to consider before conducting idiographic work of their own. Highlights: Idiographic ( n = 1) research may resolve the therapist's dilemma . There is limited guidance on how clinicians can conduct idiographic research. We provide a primer for interested clinicians and clinical scientists. This primer includes considerations for conducting idiographic research.